Induction of defense enzymes in Pseudomonas fluorescens treated chickpea roots against Macrophomina phaseolina - S.K. GOND; R.N. KHARWAR*, VINOD KUMAR, A. KUMAR, V.C. VERMA, (Indian Phytopathology, 2007)
The efficacy of various Pseudomonas fluorescens isolates was tested for the induction of systemic resistance against dry root rot of chickpea caused by Macrophomina phaseolina. Among five isolates of P. fluorescens, Pf4-99 was strong siderophore producing and plant growth promoter. This isolate also inhibited the mycelial growth of M. phaseolina in in-vitro and decreased the root rot incidence under polyhouse. In Pf4-99 treated plants, an increase in phenolic content was observed on 5thd while maximum increase in PAL activity was observed on 4th d after challenge inoculation with M. phaseolina. A marked increase in Chitinase and p-1,3-glucanase activity was observed in response to pathogen inoculation in Pf4-99 treated plants. An increase in PPO activity was observed upon challenge inoculation with pathogen. The level of PO was multifold higher up to 3-day after Pf4-99 treatment. The observations revealed that, P. fluorescens isolate Pf4-99 systemically induced resistance against dry root rot of chickpea by the accumulation of battery of enzymes in response to pathogen infection.